Considering Prose - Mayne Andrew; Shuttleworth John (Hodder & Stoughton, 1984)
This book presents such students with many new ways of tackling practical prose criticism, and offers them a combination of challenge and enjoyment, whether they are working in groups or individually. Preface, Introduction, Diction, Metaphorical Language, Rhythm, Point of View, Irony, Tone, Some Practice in Answering Examination Questions, Passages of Prose for Criticism, References to Pairings of Prose Passages, Index of Authors and Extracts.